A descriptive analysis of a medical humanitarian aid initiative for quality perinatal management in war-torn Ukraine - Iryna Mogilevkina; Dmytro Dobryanskyy; Rhona MacDonald; Diane Watson; David Southall (Conflict and Health)
Abstract Background Russian’s invasion of Ukraine has seriously disrupted perinatal care. In a humanitarian initiative, emergency obstetric and neonatal equipment and drugs were provided by Maternal and Childhealth Advocacy International and distributed by Ukrainian partners to a selected 61 maternity hospitals throughout Ukraine. The programme included engaging mothers in labour to undertake fetal heart rate monitoring using a battery operated, portable, doppler ultrasound probe. This paper describes some characteristics of participants and analyses differences in fetal distress management and maternal / neonatal outcomes following different approaches to fetal health surveillance. Methods Data from 28,808 births were collected in specially developed database which contained information on maternal characteristics, course of pregnancy and childbirth, maternal and neonatal outcomes and donated drugs and equipment used. After informed consent, mothers (n = 13735) who agreed to use in labour fetal self-monitoring in addition to standard intrapartum fetal health surveillance, monitored and recorded fetal heart rate changes on a “contraction-by-contraction” basis into a special form. Data on maternal experience with self-monitoring were collected. Cases where fetal heart rate changes were identified (n = 1434) were extracted and analysed for differences in case management and maternal and neonatal outcomes in different approaches: joint monitoring (mother plus staff, n = 901) vs. staff only monitoring (n = 533) and different actors in case of joint monitoring (mothers, n = 512, vs. staff, n = 389). Results Vacuum assisted delivery was utilised in only < 2% cases. Caesarean section rate was 27%. Mothers reported their experience with self-monitoring as great or good in 79%. Preterm deliveries were less frequent where fetal monitoring was provided by both staff and mothers jointly. In the staff plus mother group, more often lateral tilt, intravenous fluid, spontaneous vaginal and vacuum assisted delivery and less often caesarean sections were undertaken even when fetal distress alone was an indication for operative delivery at term pregnancy. Conclusion Involvement of women may help to make delivery safer for mothers as complications may be recognized earlier and appropriately treated. Overall, the data shows that despite the full-scale war in Ukraine, it remained possible for high quality perinatal health care to continue.